Rehabilitation in rheumatoid arthritis - Golus, Anna; Abramczyk, Agata; Pietsch, Julia; Chłystek, Joanna; Łakomski, Mateusz (Journal of Education, Health and Sport, 2018)
Rheumatoid arthritis is an inflammatory, chronic and progressive connective tissue disease. The causes of this disease are not fully known. About 0. 5 - 1. 5% of the population suffer from RA. This disease is more common in women. The treatment of RA should be comprehensive and include pharmacotherapy, physiotherapy and psychotherapy. It is also important to choose appropriate otropedic supplies. The presented studies indicate a positive effect of complex physiotherapeutic treatment on the reduction of pain and other symptoms of RA.